(3fWGb JWHjb bhGYO GdESfGO GdhWfjI (B/ s - (3bQfi LfjOi bQfi LfjOis; (3CTQa haG eMeO MSfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JfGhdJ gPg GdQSGdI ehVhY fWGb JWHjb bhGYO GdGSfGO GdhWfjI(B: (3MjK JeJ eYGdLJg ef NdGd aUd JegjOi h HGHjf(B: (3GgJe GdaUd GdJegjOi HJhVjM eaghe fWGb JWHjb bhGYO GdESfGO GdhWfjI(B: (3ai Mjf YGdL GdHGH GdChd fWGb JWHjb bhGYO GdESfGO GdhWfjI HGdfXQ Edi eOi EdRGejJgG, h Ted gPG GdHGH aUdjf, JfGhd GdaUd GdChd eOi EdRGejI bGYOI GdESfGO HGdfSHI ddbGVj GdhWfi, CeG GdaUd GdKGfj aJfGhd eOj EdRGejI bGYOI GdGSfGO GdhWfjI HGdfSHI ddCWQGa(B. (3h GbJUQ GdHGH GdKGfj Ydi fWGb JWHjb bhGYO GdESfGO GdhWfjI HGdfXQ Edi MGdGJ YOe EYeGdgG(B: (3h cGf Pdc ef NdGd aUdjf(B: (3YGdL GdaUd GdChd efgeG MGdGJ YOe EYeGd bGYOI GdGSfGO GdhWfjI dCSHGH afjI(B: (3ai Mjf ChVM GdaUd GdKGfi MGdGJ YOe EYeGd bGYOI GdGSfGO GdhWfjI HSHH YOe MjGO GdbGVi GdhWfis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdj (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B483-506s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3bGYOI GdESfGO s; (3bGfhf GdbGVi s; (3bhGYO GdESfGO GdhWfjIs; (3GdbhGYO GdhWfjI s; (3GdMb GdecJSH s; (3GdfXGe GdYGe s; (3GdOaY HGdJMGjd s; (3LfSjI HdO GdbGVj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs